The impact of using social media for teaching and learning in post-secondary institutes - Al-Rahmi, Waleed Mugahed; Zeki, Akram M.; Alias, Norma; Saged, Ali Ali (Kamla-Raj Enterprises, 2017)
The current paper investigates both interactivity and engagement of using social media in collaborative learning and its impact on academic performance as addressed in previous literature. In particular, the investigation of this paper is conducted in the context of learning the Quran and Hadith. Through the application of the constructivism theory, this paper attempts to examine the role of social media in encouraging academic performance through interactivity, engagement, and collaboration. To help achieve the purpose of this study, students of University of Technology Malaysia (UTM) volunteered to participate in it. Positive and significant relations were found among social media use, collaborative learning and the students’ satisfaction in the context of learning the Quran and Hadith.